The Regulatory Design of Prosecutors’ Authority in Terminating Narcotics Cases under Restorative Justice - Arrum Maryana; Setiawan Noerdajasakti; Milda Istiqomah (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
Narcotics abuse in Indonesia not only generates social and criminological problems but also raises normative challenges within the criminal justice system, particularly concerning the orientation of punishment and the prosecutorial authority of the public prosecutor. Although Law Number 35 of 2009 on Narcotics accommodates a rehabilitative approach for abusers and addicts, law enforcement practices remain dominated by a repressive paradigm that prioritizes imprisonment, thereby creating legal uncertainty. This study aims to analyze the weaknesses in the regulation of prosecutorial authority in the termination of narcotics cases and to formulate a future regulatory design based on restorative justice. The research employs a normative legal method using statutory and conceptual approaches through the examination of primary and secondary legal materials. The findings indicate that Article 65 letter (f) of the Indonesian Criminal Procedure Code remains general in nature, lacks specific juridical parameters for narcotics cases, and has not been harmonized with the Narcotics Law. In addition, the inconsistency of terminology and the elasticity of the provisions in Articles 111 and 112 create room for multiple interpretations. Therefore, a more specific, integrated, and rehabilitation-oriented normative reconstruction is required to ensure legal certainty and enhance the effectiveness of the criminal justice system. Such reformulation is expected to strengthen the legitimacy of prosecutorial authority as dominus litis and encourage a shift in narcotics law enforcement from a purely repressive approach toward a more humane, proportional, and sustainable paradigm in line with responsive and inclusive national criminal law reform.